The Effect of Leadership Styles and Organisational Culture on Organisational Commitment and Their Impact on The Performance of Staff at The Secretariat ff The Regional People’s Representative Council of Muaro Jambi Regency - Sudirman Sudirman; Arna Suryani; Asikin Asikin; Muhammad Syukri; Ahmadi Ahmadi (Green Publisher, 2026)
Employee performance is a crucial factor in the success of public sector organizations. Although various studies have shown that leadership style and organizational culture influence employee performance, previous research findings have been inconsistent, particularly regarding the direct influence of leadership style on performance and the role of organizational commitment as a mediating variable. This study aims to analyze the influence of leadership style and organizational culture on employee performance through organizational commitment at the Muaro Jambi Regency DPRD Secretariat. The study employed a quantitative approach with a survey method through questionnaires distributed to employees. Data were analyzed using PLS-SEM to test the direct and indirect relationships between variables. The results showed that leadership style and organizational culture had a positive and significant effect on organizational commitment. Organizational culture and organizational commitment also had a positive and significant effect on employee performance. Conversely, leadership style did not have a significant direct effect on employee performance. However, organizational commitment was shown to mediate the influence of leadership style and organizational culture on employee performance. These findings indicate that improving employee performance is more effectively achieved through strengthening organizational culture and organizational commitment than through direct leadership style. The novelty of this research lies in the empirical evidence that organizational commitment acts as a mediating mechanism that explains why leadership style does not have a direct effect on employee performance in public sector organizations, especially in the Muaro Jambi Regency DPRD Secretariat.